Study of the surface quality of carbon fiber–reinforced thermoplastic matrix composite (CFRTP) machined by abrasive water jet (AWJM) - Bañón-García, Fermín; Sambruno, Alejandro; Batista, Moisés; Simonet, Bartolomé; Salguero, Jorge (Springer Nature, 2020)
Carbon fiber-reinforced thermoplastics (CFRTP) have great interest nowadays due to their excellent mechanical properties and lightness. However, in opposition to thermoset matrix composites, there is a lake in the research about machining processes of these materials. Their low glass transition temperature is a handicap when conventional machining is used. An alternative is abrasive water jet machining (AWJM) because it does not cause thermal damage. However, the surface quality produced by this process must be studied and related to the cutting parameters. This article studies the surface quality generated by water jet machining in a low melting point thermoplastic matrix composite material. The kind of thermoplastic used is a TPU (polyure- thane). The combination of a high-strength material (carbon fiber) with a low-strength material (thermoplastic matrix) makes machining difficult and can generate a poor surface finish. The influence of cutting parameters has been evaluated through an ANOVA analysis. A mathematical model that relates the surface quality with the cutting parameters has been established by means of a response surface methodology (RSM). The combination of a hydraulic pressure of 250 MPa with a traverse speed of 300 mm/min and an abrasive mass flow of 170 g/min produces the best surface quality. Finally, the main flaws when CFRTP is water jet machined have also been identified.
https://openpolicyfinder.jisc.ac.uk/id/publication/13456
Keywords: Plásticos reforzados; AWJM; CFRTP; Surface Quality; RSM; ANOVA; C/TPU